1985
DOI: 10.1177/001872088502700607
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Age Profile: An Objective Decision Criterion for the Assessment of Pilot Performance Capacities and Capabilities

Abstract: The initial development of a computer-based information-processing performance battery with aviation-relevant task structures is reported. It is shown that the currently existing prototype is sensitive to individual differences within chronological age groups as well as to age-related changes across different age groups. The utilization of such a test battery for the longitudinal assessment of aviator performance capabilities is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
25
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 7 publications
8
25
0
Order By: Relevance
“…In addition, a significant sequence effect on landing decision was found. Pilots who completed the Land, No Land, Land sequence made more accurate decisions across the three trials than pilots who completed the Land, Land, No Land sequence (χ 2 (2) = 11.85, P = 0.003). Importantly, no sequence or age by expertise group difference was found in the first trial, in which all subjects had a Land scenario (Land, Land, No Land hit rate: 61.77%; Land, No Land, Land hit rate: 65.79%).…”
Section: Resultsmentioning
confidence: 98%
“…In addition, a significant sequence effect on landing decision was found. Pilots who completed the Land, No Land, Land sequence made more accurate decisions across the three trials than pilots who completed the Land, Land, No Land sequence (χ 2 (2) = 11.85, P = 0.003). Importantly, no sequence or age by expertise group difference was found in the first trial, in which all subjects had a Land scenario (Land, Land, No Land hit rate: 61.77%; Land, No Land, Land hit rate: 65.79%).…”
Section: Resultsmentioning
confidence: 98%
“…These include age-related increases in switching costs when participants have to alternate between two auditory or visual channels (Braune & Wickens, 1985;Panek, Barrett, Sterns, & Alexander, 1977;Wickens, Braune, & Stokes, 1987). In addition, investigators have also observed increased switching costs for older adults on tasks such as addition and subtraction or providing antonyms and synonyms (Botwinick, Brinley, & Robbin, 1958;Brinley, 1965;Schaie, 1958).…”
Section: Aging and Task Switchingmentioning
confidence: 99%
“…Braune and Wickens (1986) conclude that spatial ability, dichotic listening and perceptual-motor co-ordination decrease together with reaction time in pilots beyond the age of forty.…”
Section: Discussionmentioning
confidence: 78%